Effect of Mirror Therapy Combined with Task-Oriented Training on Hemiplegic Upper Limb Functions after Stroke - HE Aiqun; WANG Yang; NIE Tiancui; YING Qixing; YE Simei; SONG Qiushuang; XU Hui; HE Maoli (康复学报, 2022)
ObjectiveTo investigate the priming effect of mirror therapy combined with task-oriented training on hemiplegic upper limb functions after stroke.MethodsA total of forty eligible inpatients with stroke were divided into observation group and control group according to the random number table method, with 20 cases in each group. The conventional rehabilitation training was used in both groups. The control group was given upper limb task-oriented training 30 min per day in addition to conventional rehabilitation; the observation group was given mirror therapy 30 min per day in addition to the control group, both 5 days per week for 4 consecutive weeks. Assessments were administered at baseline and immediately after all the intervention. The upper limb motor functions were assessed by the Fugl-Meyer assessment-upper extremity (FMA-UE) and action research arm test (ARAT), occupational performance was assessed by the functional test of hemiplegic upper extremity-Hong Kong (FTHUE-HK).ResultsThere were no significant differences in FMA-UE scores, ARAT scores and FTHUE-HK grade between the two groups before treatment (P>0.05). After 4 weeks of treatment, the FMA-UE scores, ARAT scores of the two groups showed significant improvement compared with those before treatment (P<0.001), FTHUE-HK grade of the two groups showed significant improvement compared with that before treatment (P<0.05). The improvement degree of FMA-UE scores (11.40±6.29) in the observation group was more significant than that (5.05±3.35) in the control group (P<0.001), the improvement of ARAT scores (6.25±3.67) in the observation group was more significant than that (3.25±2.73) in the control group (P<0.05), the improvement of FTHUE-HK grade in the observation group was more significant than that in the control group (P<0.05).ConclusionMirror therapy, combined and as priming for task-oriented training, can produce clinical improvements in upper extremity function and occupational performance in patients with hemiparesis after stroke.